Association of the gut microbiome with fecal short-chain fatty acids, lipopolysaccharides, and obesity in young Chinese college students - Song, Baokuo; Zhao, Kexin; Zhou, Shuaikang; Xue, Yuling; Lu, Han; Jia, Xianxian; Wang, Shijie (Frontiers in Nutrition, 2023)
Obesity is a growing health problem among young people worldwide, and studies have shown that it is associated with host gut conditions. Therefore, this study aimed to explore the relationship among obesity, intestinal microbiota, fecal short-chain fatty acids (SCFAs), and lipopolysaccharide (LPS) in young college students. To this end, 16S rRNA gene sequences, SCFA and LPS contents, and obesity status were analyzed in 68 young college students (20–25 years old). Of note, there were significant differences in intestinal microbial beta diversity among students with different body mass index (BMI). The abundance and proportion of Firmicutes and Bacteroides had no significant correlation with BMI. The contents of butyric acid and valeric acid in the feces of obese students were low, and the content of SCFAs had no significant correlation with BMI and LPS. The content of LPS in the feces of obese people was significantly higher than that in healthy people, and there was a significant positive correlation between LPS content and BMI. In general, there was a correlation among intestinal microbiota, SCFA, LPS, and BMI in young college students. Our results may enrich the understanding of the relationship between intestinal conditions and obesity and contribute to the study of obesity in young college students.